2023
DOI: 10.1186/s12916-023-02754-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between progression-free survival and overall survival in women receiving first-line treatment for metastatic breast cancer: evidence from the ESME real-world database

Abstract: Background Overall survival (OS) is the gold standard endpoint to assess treatment efficacy in cancer clinical trials. In metastatic breast cancer (mBC), progression-free survival (PFS) is commonly used as an intermediate endpoint. Evidence remains scarce regarding the degree of association between PFS and OS. Our study aimed to describe the individual-level association between real-world PFS (rwPFS) and OS according to first-line treatment in female patients with mBC managed in real-world sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Breast cancer patients with HER-2 overexpression are 4,889 times more at risk of developing brain metastases compared to HER-2-negative patients. Tumors with HER-2 overexpression have a significantly higher risk of distant metastasis compared with HER-2-negative tumors and show a higher potential for central nervous system and lung metastases and a low risk of recurrence and the development of bone disease [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer patients with HER-2 overexpression are 4,889 times more at risk of developing brain metastases compared to HER-2-negative patients. Tumors with HER-2 overexpression have a significantly higher risk of distant metastasis compared with HER-2-negative tumors and show a higher potential for central nervous system and lung metastases and a low risk of recurrence and the development of bone disease [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with trastuzumab monotherapy, the ORR was significantly higher for the pyrotinib and trastuzumab plus docetaxel regimen (OR: 46.58, 95% CrI: 1.78–1176.63) and the trastuzumab and docetaxel regimen (OR: 13.00, 95% CrI: 1.19–142.27). When evaluated using linear regression analysis, a strong correlation was found between PFS and OS in the first‐line treatment of metastatic breast cancer [ 39 , 40 ]. However, no correlation between ORR and OS could be confirmed, implying that ORR results may not translate into OS.…”
Section: Discussionmentioning
confidence: 99%
“…However, as expected, this correlation is stronger than that for other breast cancer subtypes. A more recent study using real-world data also showed inconsistent but poor correlation between PFS and OS in advanced breast cancer in different subtypes at individual-level [13].…”
Section: Surrogate Endpoints In Advanced Breast Cancermentioning
confidence: 98%